Theileriosis: Progress towards vaccine development through understanding immune responses to the parasite - Morrison, W. Ivan; Taracha, E.L.N.; McKeever, Declan J. (Elsevier, 1995)
Studies of the immune responses of cattle to Theileria parva have provided evidence that immunity to the parasite can operate at two levels, namely the sporozoite and the schizont-infected lymphoblast. Antibodies that neutralize the infectivity of sporozoites have been detected in the serum of hyperimmunized cattle, and a recombinant sporozoite surface antigen has been shown to induce neutralizing antibodies and protection against experimental challenge. However, the immunity that develops following primary infection with T. parva is accompanied by only low levels of antibodies to sporozoites; there is overwhelming evidence that under these circumstances protection is mediated by T cell responses against infected lymphoblasts. Potent class IMHC-restricted cytotoxic T lymphocyte (CTL) responses are detected in animals recovering from infection and treatment or challenge infections. Two recent findings have provided direct evidence for the importance of these responses in immunity. First, the strain specificity of CTL in cattle immunized with one stock of the parasite was found to correlate with the subsequent susceptibility of individual animals to challenge with a heterologous cloned parasite population. Second, the adoptive transfer of lymphocytes highly enriched for CD8 plus T cells, from immune to naive identical twin calves, was found to protect against experimental challenge. The CTL response in individual animals appears to be directed towards a limited number of antigenic epitopes. The antigenic specificity is determined in part by class I MHC phenotype although there is evidence that other phenomena such as antigenic competition are also involved. Current efforts are directed towards identification of the parasite antigens recognized by CTL with the eventual aim of exploring their potential for vaccination.